Pengelolaan Excellent Service di SMK Negeri 2 Wonogiri - Sulistianto, Heri; , Dr. Sabar Narimo, M.M., M.Pd; , Dr. Djalal Fuadi, M.M (2017)
The purposes of conducting this study are : (1) Identifiying how to plan the excellent service in SMK Negeri 2 Wonogiri. (2) Identifiying the implementation of excellent service in SMK Negeri 2 Wonogiri. (3) Identifiying the evaluation of excellent service implementation in SMK Negeri 2 Wonogiri. The techniques of collecting data apply with a depth interviews, observations and documentations. The dataanalysis uses descreptive-quality analysis model. The resultsof the study are : (1) the excellent service in SMK Negeri 2 Wonogiri is conducted by a good planning and regulary. The excellent service planning is adjusted to the priority on the quality objectives set by the princopal that has been designed by each line of work, then formulated the planning in order to APBS adjusted to the conditions how can improve the excellent service. (2) The implementation of excellent service in SMK Negeri 2 Wonogiri in the field of curiculum according to the latest government regulations and conducted well will make the learning process more effectively and efficiently, in the field of student affairs, the enactment and enforcement dicipline for students are done gradually and countinously, also the choice of extracurricular activities are implemented to channel the talents and interests of learners outside school hours, in the field of facilities and infrastructure, it always completes the building and educational facilities continually. In the field of public relations that is by estabilishing communication with the industrial world as much as possible so that it can be used for job training process, work apprenticeship as well as presenting guest teacher, in the field of administration is the establisment of documentations and service system for the tecaher and learners.(3) Evaluation is carried out periodically,weekly, monthly, every quarter of every semester or the end of the school year, the process is adapted to the field conditions. A thorough evaluation of the implementation of excellent service at SMK Negeri 2 Wonogiri is conducted in management review activities annualy as part of the ISO 9001 : 2008 quality management system proces in which there are inputs from costumers that effect the improvement of school services greatly.